Safe Human-Robot Cooperation in an Industrial Environment. (10th January 2013) - Pedrocchi, Nicola; Vicentini, Federico; Matteo, Malosio; Tosatti, Lorenzo Molinari
The standard EN ISO10218 is fostering the implementation of hybrid production systems, i.e., production systems characterized by a close relationship among human operators and robots in cooperative tasks. Human-robot hybrid systems could have a big economic benefit in small and medium sized production, even if this new paradigm introduces mandatory, challenging safety aspects. Among various requirements for collaborative workspaces, safety-assurance involves two different application layers; the algorithms enabling safe space-sharing between humans and robots and the enabling technologies allowing acquisition data from sensor fusion and environmental data analysing. This paper addresses both the problems: a collision avoidance strategy allowing on-line re-planning of robot motion and a safe network of unsafe devices as a suggested infrastructure for functional safety achievement.